Safety and efficacy of levetiracetam for the treatment of partial onset seizures in children from one month of age - Cormier J (Dove Medical Press, 2013)
Justine Cormier, Catherine J ChuMassachusetts General Hospital, Department of Neurology, Programs in Child Neurology and Neurophysiology, Boston, MA, USAAbstract: Epilepsy is a common neurological disorder in the pediatric population, affecting up to one percent of children, and for which the mainstay of treatment is anticonvulsant medication. Despite the frequent use of anticonvulsant drugs, remarkably little is known about the safety and efficacy of most of these medications in the pediatric epilepsy population. Of 34 anticonvulsants currently approved for use by the US Food and Drug Administration (FDA), only 13 have been approved for use in children. Although infants and young children are disproportionately affected by epilepsy, there are currently only three anticonvulsant medications that have been specifically evaluated and approved for use in children younger than 2 years of age. In 2012, the FDA approved levetiracetam as an adjunctive treatment for partial onset seizures in infants and children from one month of age. Here we review the available data on levetiracetam in the pediatric epilepsy population. We first discuss the pharmacological profile of levetiracetam, including its mechanism of action, formulations and dosing, and pharmacokinetics in children. We then review the available efficacy, safety, and tolerability data in children from one month of age with partial onset seizures. We conclude that the current data leading to the approval of levetiracetam for use in infants and children with partial onset seizures is encouraging, although more work needs to be done before definitive conclusions can be drawn about the efficacy of levetiracetam across different pediatric age groups.Keywords: levetiracetam, anticonvulsant drug, partial seizures, pediatric epilepsy